Analysis of p16 gene mutations and deletions in childhood acute lymphoblastic leukemias - Lemos, José Alexandre Rodrigues; Defavery, Ricardo; Scrideli, Carlos Alberto; Tone, Luiz Gonzaga (São Paulo Medical Journal, 2003)
CONTEXT: The p16 tumor suppressor gene encodes a cyclin-dependent kinase 4 inhibitor that blocks cell division during the G1 phase of the cell cycle. Alterations in this gene have been reported for various neoplasia types, including acute lymphoblastic leukemias (ALL), especially T-cell acute lymphoblastic leukemias (ALL). OBJECTIVE: To determine probable alterations in the p16 gene in children with acute lymphoblastic leukemias using the polymerase chain reaction (PCR) and direct DNA sequencing and also to analyze event-free survival (EFS). DESIGN: Retrospective study. SETTING: Department of Child Care and Pediatrics, Faculty of Medicine of Ribeirão Preto, Universidade Federal de São Paulo. PARTICIPANTS: Fifty-six children with ALL (mean age 4 years). Forty (71.43%) had B-cell and 12 (21.43%) had T-cell ALL; 4 (7.1%) were biphenotypic. SAMPLE: DNA samples were extracted from bone marrow upon diagnosis and/or relapse. In 2 T-cell cases, DNA from cerebrospinal fluid (CSF) was analyzed. MAIN MEASUREMENTS: Deletions or nucleotide substitutions in exons 1, 2 and 3 of the p16 gene were determined by PCR and nucleotide sequencing. Event-free survival was determined by the Kaplan-Meyer and log-rank test for patients carrying normal and altered p16. RESULTS: Deletions in exon 3 were observed in five cases. Abnormal migration in PCR was observed in seven cases for exon 1, six for exon 2, and five for exon 3. Mutations in exon 1 were confirmed by direct DNA sequencing in four cases and in exon 2 in two cases. The Kaplan-Meyer survival curves and the log-rank test showed no significant differences in 5-year EFS between children with normal or altered p16, or between patients with BALL carrying normal or altered p16 gene. Patients with T-ALL could not be evaluated via Kaplan-Meier due to the small number of cases. CONCLUSIONS: Our results, particularly regarding deletion frequency, agree with others suggesting that deletions in the p16 are initial events in leukemia genesis. The small number of samples did not allow stablishment of correlation between childhood ALL and the p16 point mutations found in our study. Kaplan-Meier analysis revealed no significant correlation between EFS and alterations in ALL. The p16 alterations frequency observed for B and TALL agreed with reports from other centers.